2004
DOI: 10.1289/ehp.7209
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Environmental Concentrations of the Pharmaceutical Ethynylestradiol Causes Reproductive Failure in Fish

Abstract: Heightened concern over endocrine-disrupting chemicals is driven by the hypothesis that they could reduce reproductive success and affect wildlife populations, but there is little evidence for this expectation. The pharmaceutical ethynylestradiol (EE2) is a potent endocrine modulator and is present in the aquatic environment at biologically active concentrations. To investigate impacts on reproductive success and mechanisms of disruption, we exposed breeding populations (n = 12) of zebrafish (Danio rerio) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
345
5
11

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(378 citation statements)
references
References 64 publications
17
345
5
11
Order By: Relevance
“…However, significant induction of Vtg was only found in the males fed with pellet food for the adult fish of generation F0 in the present study. The observation was similar with the result reported by Nash et al (2004). It may be an acclimation to the long-term exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, significant induction of Vtg was only found in the males fed with pellet food for the adult fish of generation F0 in the present study. The observation was similar with the result reported by Nash et al (2004). It may be an acclimation to the long-term exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Reproductive performance has been considered to be a key parameter affecting the stabilization of fish populations. In recent years, many studies have found that the reproductive success of fish has been impaired after exposed to different pollutants (Mills et al, 2003;Nash et al, 2004). Länge et al (2001) demonstrated that there was a general trend toward a decrease in spawning in fathead minnow after EE 2 long-term exposure at 0.2 and 1 ng L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations above 1 ng L −1 of EE2 also induced higher vitellogenin plasma lev-els in both males and females [149,150]. Nash et al [151] registered similar findings for zebrafish males by simply performing the assay with 0.5 ng L −1 of EE2. Life-long exposure of zebrafish to 5 ng L −1 of EE2 has led to reproductive failure due to the absence of sec-ondary male sex characteristics and normal testes [151].…”
Section: Sex Hormonesmentioning
confidence: 68%
“…This is the first report to describe that the sex ratio in zebrafish is male biased in response to TBP exposure, and this observation suggests that long-term exposure to TBP affects sex differentiation and sex determination in zebrafish. Indeed, teleost populations exposed to estrogenic compounds showed skewing of the sex ratio in favor of females (Metcalfe et al, 2001;Lange et al, 2001;Nash et al, 2004;Zhong et al, 2005;Zha et al, 2008). The changes in sex ratios to femalebiased types are known to be caused by the transformation of the testis to ovaries under the direct influence of environmental estrogen during early gonadal development (Lange et al, 2001;Nash et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, teleost populations exposed to estrogenic compounds showed skewing of the sex ratio in favor of females (Metcalfe et al, 2001;Lange et al, 2001;Nash et al, 2004;Zhong et al, 2005;Zha et al, 2008). The changes in sex ratios to femalebiased types are known to be caused by the transformation of the testis to ovaries under the direct influence of environmental estrogen during early gonadal development (Lange et al, 2001;Nash et al, 2004). Therefore, the balance between estrogens and androgens is crucial for sex differentiation in fish; the inhibition of aromatase suppresses estrogen formation, thereby disturbing the normal sex ratio and resulting in a male-dominant population.…”
Section: Discussionmentioning
confidence: 99%